Síndrome de burnout en trabajadoras sexuales: una mirada a través de la jurisprudencia colombiana (2018)
Sex work is understood as the exchange of sexual activity in exchange for money, when it is exercised voluntarily by people of legal age. It is a term used as a synonym and preferably in place of prostitution, however, implies that there must be a regulation regarding such activity. Likewise, the occupational risks of this trade, such as the burnout syndrome, are unknown aspects. Therefore, the main objective was to examine the burnout syndrome and the jurisprudential line of sex work in Colombia. On the one hand, a revision of the legal framework was carried out and, on the other hand, the burnout syndrome was evaluated in a sample composed of 59 sex workers. All women completed a sociodemographic questionnaire and the Utrecht Burnout Scale for the Contactual professions (UBOS-C). After reviewing the legal framework is found that there is a gap in the regulation of sex work, however there are rules both prohibitionists and regulators and also there is a landmark judgment (T-629 of 2010) that somehow regulates and deals to ensure the rights of sex workers. As for the burnout syndrome, it is found that the participants of the present investigation report medium-high levels of emotional exhaustion, depersonalization and personal competence. In addition, there is a negative and statistically significant relationship between the level of monthly income and the burnout syndrome. Specifically, a higher level of monthly income was associated with a lower level of emotional exhaustion. The results are discussed, pointing out the importance of the State setting up a law regulating this activity taking into account different social agents and from an interdisciplinary perspective